Facile Synthesis and Photocatalytic Property of Titania/Carbon Composite Hollow Microspheres with Bimodal Mesoporous Shells - Guohong Wang; Bei Cheng; Jun Zhang; Lin Xu; Tingting Yin (International Journal of Photoenergy)
Titania/carbon composite hollow microspheres with bimodal mesoporous shells are one-pot fabricated by hydrothermal treatment of the acidic (NH4)2TiF6 aqueous solution in the presence of glucose at 180∘C for 24 h and then calcined at 450∘C. The as-prepared samples were characterized by XRD, SEM, TEM, HRTEM, UV-visible spectroscopy, and nitrogen adsorption-desorption isotherms. The photocatalytic activity of the as-prepared samples was evaluated by daylight-induced photocatalytic decolorization of methyl orange aqueous solution at ambient temperature. The effects of calcination time on the morphology, phase structure, crystallite size, specific surface area, pore structures, and photocatalytic activity of the microspheres were investigated. The results indicated that the as-obtained TiO2/C composite hollow spheres generally exhibit bimodal mesopore size distribution with their peak intra-aggregated mesopore size in the range of 2.3–4.5 nm and peak interaggregated mesopore size in the range of 5.7–12.7 nm, depending on specific calcination time. The daylight-induced photoactivity of as-obtained hollow TiO2/C microspheres generally exceeds that of Degussa P25. The influences of calcination time on the photoactivity are discussed in terms of carbon content, phase structures, and pore structures.